Leaders of the Americas 2 - P.Pickett William (McGraw -Hill, 2004)
Leaders of the Americas is an intermediate and high-intermediate two-book supplementary reading and vocabulary series. Students learn about historical figures of North and South America while improving their core reading skills, building vocabulary, and practicing test taking.